Objective evaluation of seat discomfort on eRacing performance. - Vanheusden, Frederique J; Ogilvie, Molly O (Work, 2026)
Background: While physical and mental health training guidelines have received much attention and scientific scrutinisation for traditional sports, these guidelines have not yet been developed for electronic sports (eSports). One important factor for developing these guidelines is to find appropriate ways to objectively measure performance and wellbeing of eSport participants through a combination of behavioural and physiological measurements. Objective: To determine the effect of perceived discomfort on stress levels and task performance during racing simulation (eRacing) activities using physiological and behavioural measurements. Methods: Discomfort and stress were analysed using questionnaires, electro-encephalography, electrocardiography, and galvanic skin response while 17 participants engaged in off-line Assetto Corsa racing simulation competitions. Results: Discomfort slightly increased with prolonged seating, and perceived task difficulty significantly increased stress and self-assessed task performance. While significant differences could be observed in electro-encephalographic (EEG) alpha-, beta-band activity and galvanic skin responses (GSR) data, these were not correlated to perceived stress, discomfort, or performance. Conclusions: This study showed the potential for using physiological measurements to monitor eSport player performance before, after and during eRacing activities. While no significant correlations with behavioural assessments were found, further studies could build on the suggested physiological markers to determine effects of competitive environments on eSport participants' wellbeing.